2001
DOI: 10.1002/1097-0142(20011115)92:10<2603::aid-cncr1613>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Short tandem repeat polymorphism linkage to the androgen receptor gene in prostate carcinoma

Abstract: BACKGROUND Due to high polymorphism, common sequences, and ubiquitous presence, short tandem repeats (STRs) may enhance genomic typing to determine prostate carcinoma (CaP) predisposition. The human phosphoglycerate kinase (PGK1) gene is located within Xq11‐Xq13, a region implicated in familial prostate carcinoma, androgen insensitivity, perineal hypospadias, and other genitourinary abnormalities. The PGK1 STR is the most polymorphic site described in the Xq11‐Xq13 interval and was investigated for its ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…PGK1 is located in a chromosomal region associated with familial prostate cancers, hypospadias, and androgen insensitivity (X chromosome; Xq11-Xq13; ref. 7). In the nucleus, PGK1 influences DNA replication and repair.…”
Section: Introductionmentioning
confidence: 99%
“…PGK1 is located in a chromosomal region associated with familial prostate cancers, hypospadias, and androgen insensitivity (X chromosome; Xq11-Xq13; ref. 7). In the nucleus, PGK1 influences DNA replication and repair.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Therefore, isoflavone with its specific targeting effect on was found in PCa. 29,30 In our study, we found that the expression of PGK-1 was upregulated and the expression of miR-1256 was downregulated in PCa cells and in human prostate tumor tissues. Transfection of miR-1256 mimic into PCa cells inhibited the expression of PGK-1, suggesting that PGK-1 could be a target of miR-1256.…”
Section: Discussionmentioning
confidence: 49%
“…22 The expansion and instability of STRs, especially the trimeric repeats, in the coding region of disease related genes have been thought to be the directed and major reason for many neurological disorders, for example, Huntington disease, Ataxia, Kennedy disease, SCA-1, SCA-3 and Smith disease, et al 23,24 There are several reports about the association of STRs in the prostate cancer related genes with the risk of the cancer, and on the bases of the joint effect of several loci, people want to construct a risk profile for the diagnosis, treatment and prognosis of prostate cancer ultimately. 16,25,26 The prevalence of the somatic instability for polymorphism of tetra-and penta-nucleotide STRs in gastric cancer has been studied, 27 but there is no report about the STRs in esophageal cancer related genes. Our findings of TCA STR in ECRG2 and the polymorphism frequencies in population may give clues for a pilot study of carcinogenesis and development of esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…15 Owing to high polymorphism, common sequences and ubiquitous presence, STRs were also used in detecting predisposition to tumors, such as prostate cancer. 16 However, to our best …”
mentioning
confidence: 82%
See 1 more Smart Citation